As an alternative to the solution above, working with the two equations you have been given, use substitution to solve.

`therefore p+q=11` becomes `p=11-q` when rearranged which now substitute into the other equation:

`therefore pq=18` becomes `(11-q) times q = 18`

`therefore 11q -q^2 = 18`

`therefore 0 = q^2-11q+18` (Note the...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

As an alternative to the solution above, working with the two equations you have been given, use substitution to solve.

`therefore p+q=11` becomes `p=11-q` when rearranged which now substitute into the other equation:

`therefore pq=18` becomes `(11-q) times q = 18`

`therefore 11q -q^2 = 18`

`therefore 0 = q^2-11q+18` (Note the equation has been rearranged)

Solve by factorizing using the first term's factors (q x q) and the third term's factors which will render a middle term of -11; ie -9 x -2:

`therefore 0= (q-2)(q-9)`

`therefore q=2` or `q=9`

Solving for p(pq=18) or (p+q=11) shows that p and q are interchangeable:

**Ans:**

**Therefore when q=2, p=9 and when q=9, p=2 **